Usage of possibilities AutoCAD 2010 in operation of the engineer-designer - Поморцева, Елена Евгеньевна (Eastern-European Journal of Enterprise Technologies, 2012)
Questions of an intensification of work of the designers using at designing AutoCAD are considered. Passage to new level of designing at the expense of usage of new possibilities of version 2010 will allow to spare considerably time and to receive real incomes.